Mesenteric Ischemia and Myocardial Infarction Associated with Atrial Fibrillation. (1st April 2018) - Cheng, Liting; Wu, Yongquan
Abstract : Atrial fibrillation is a common disease correlated with embolism incidents. However, there is lack of report on atrial fibrillation causing myocardial infarction and mesenteric ischemia at the same time. Our patient is a 69-year-old woman who had undergone thoracic surgery a month before presented to our hospital with newly discovered atrial fibrillation, abdominal pain, and ST-elevated myocardial infarction. This is a rare case that atrial fibrillation took place one month after surgery and caused embolism incidents in both coronary artery and mesenteric artery.